2001
DOI: 10.1073/pnas.131214798
|View full text |Cite
|
Sign up to set email alerts
|

Three SNARE complexes cooperate to mediate membrane fusion

Abstract: Soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) proteins of the syntaxin, SNAP-25, and VAMP families mediate intracellular membrane fusion through the formation of helical bundles that span opposing membranes. Soluble SNARE domains that lack their integral membrane anchors inhibit membrane fusion by forming nonfunctional complexes with endogenous SNARE proteins. In this study we investigate the dependence of membrane fusion on the concentration of a soluble SNARE coil domain deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
132
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(159 citation statements)
references
References 30 publications
(43 reference statements)
23
132
2
Order By: Relevance
“…Because we observe this high variability with neuronal SNAREs at constant density but different curvature, a corollary of this conclusion is that we would expect that cooperativity of SNAREs involved in other trafficking pathways will also be highly variable, not because of their inherent biochemical properties, but rather owing to the particular biophysical characteristics of the trafficking vesicle. We therefore suggest that the reported estimates of numbers of involved SNARE complexes likely reflect the particular type of fusion studied and that there is no universally conserved number, as has been often assumed (13,(15)(16)(17)(18)33).…”
Section: Discussionmentioning
confidence: 89%
“…Because we observe this high variability with neuronal SNAREs at constant density but different curvature, a corollary of this conclusion is that we would expect that cooperativity of SNAREs involved in other trafficking pathways will also be highly variable, not because of their inherent biochemical properties, but rather owing to the particular biophysical characteristics of the trafficking vesicle. We therefore suggest that the reported estimates of numbers of involved SNARE complexes likely reflect the particular type of fusion studied and that there is no universally conserved number, as has been often assumed (13,(15)(16)(17)(18)33).…”
Section: Discussionmentioning
confidence: 89%
“…Functional studies have clearly indicated that multiple SNARE complexes cooperate to bring about an individual vesicular fusion event (Hua and Scheller, 2001;Keller and Neale, 2001;Han et al, 2004;Keller et al, 2004;Montecucco et al, 2005), with the number of participating complexes possibly affecting the speed of opening, or the diameter of the fusion pore (Han et al, 2004). Although oligomerization may be an inherent feature of SNARE complexes, a detailed description of how such interactions take place and their relevance for membrane fusion has been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Because PC12 cells display Ca 2ϩ -evoked secretion that requires cooperativity between three or more SNARE complexes (Hua and Scheller, 2001), expression of fulllength syb2 mutants that are incorporated into SNARE complexes of normal stability but impaired in dimer formation should generate a dominant-negative phenotype, revealing a potential role for SNARE complex dimerization in membrane fusion. PC12 cells were transfected with syb2 and hGH as described above, and intact cells were assayed directly to measure constitutive and evoked exocytosis.…”
Section: Dominant-negative Secretory Effects Of Syb2 Dimerization Mutmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vivo experimental evidence for multimerization comes from the cooperative action of the SNAREs as well as the dose dependence of inhibition by peptide blocker and the botulinum neurotoxins. Together the evidence has suggested multimers containing between 3 and 15 SNARE complexes (Han et al, 2004;Hua and Scheller, 2001;Montecucco et al, 2005;Raciborska et al, 1998;Rickman et al, 2005;Stewart et al, 2000). Nonetheless, at present working models for multimerization are quite preliminary and how they might aid in fusion is unknown.…”
Section: Snare-based Fusionmentioning
confidence: 99%